Fighting fire! : ten of the deadliest fires in American history and how we fought them - Cooper, Michael L., 1950- (Henry Holt and Company, 2014)
Examines ten of the deadliest infernos this nation has ever endured: the great fires of Boston, New York, Chicago, Baltimore, and San Francisco; the disasters of the Triangle Shirtwaist Factory, the General Slocum, and the Cocoanut Grove nightclub; the wildfire of Witch Creek in San Diego County; and the catastrophe of 9/11.